Development of In-House MOS transistor at KUKUM Micro Fabrication Cleanroom: Microelectronic undergraduate activities - Marlia, Morsin; Nur Hamidah, Abdul Halim; Uda, Hashim; Hashim, Saim (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.